A Comparative Analysis of Green Finance Awareness in Poland and Romania - SIEMIONEK-RUSKAŃ, Małgorzata; LEPCZYŃSKI, Błażej; FANEA-IVANOVICI, Mina (Journal of Environmental Management and Tourism; Vol 13 No 7 (2022): JEMT, Volume XIII, Issue 7(63), Winter 2022DO - 10.14505/jemt.v13.7(63).02, 2022)
In the context of the European Green Deal, green finance represents an important development in the financial landscape. We hereby do a comparative analysis of perceptions and awareness in terms of green finance products and future demand for green finance in Poland and Romania, the two largest CEE EU countries. Using a survey (n=363), we identify the main similarities and differences between the two categories of respondents. More than a half of the respondents from each country are interested in green finance activities. While for most issues, Polish and Romanians provide similar answers, there is a big discrepancy in the level of awareness regarding green finance, which is higher in Poland. The similarity resides from the side of the main benefits resulting from implementing green financial instruments by companies. Both Polish and Romania respondents choose cost savings and improving company’s image as the factors with highest importance. We then discuss the main research and practical implications.